ANALISIS STRATEGI PENENTUAN HARGA SEWA KAMAR SELAMA PANDEMI COVID-19 BERDASARKAN METODE OUT OF POCKET COST TERHADAP BISNIS HOTEL DI TANJUNG SELOR KABUPATEN BULUNGAN STUDI KASUS GRAND PANGERAN KHAR HOTEL) - Febriati Sari; Dwiyani Sudaryanti; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2022)
Tanjung Selor is one of the cities with high hotel growth in North Kalimantan, because it is the closest shopping center and is easy to reach by vehicle by land. Therefore, many visitors from various sub-districts stay at the Tanjung Selor hotel. With so many hotel industries in Tanjung Selor, competition in terms of price, facilities, and services is bound to exist. Every hotel is competing to provide the best so that its hospitality business is not less competitive with other hotel businesses. Moreover, during the current Covid-19 pandemi, the hotel manager needs to carry out the right strategy so that it is not empty of visitors during this pandemi. This study aims to find out how much is the room rental price during the Covid-19 pandemi at the Grand Pangeran Khar Hotel based on out of pocket cost. Based on the calculation results, it can be seen that the selling price during the covid-19 pandemi set by the Grand Pangeran Khar Hotel for the Pangeran, Boelungon, Family, Executive, Deluxe, Superior, and Standard types is able to cover the cost of the existing rental cost, but for the type of room Executive gets the lowest profit from other room types.Keywords: determination of rental price, Out Of Pocket Cost, Cash cost